Avaliação do efeito de agentes hidrofugantes nas características de telhas onduladas de fibrocimento sem amianto - Coelho, Tassiane de Paula Pinheiro (2019)
The fiber cement is a material of great applicability in the branch of the civil construction, due to its characteristics, versatility and low cost, that makes it an accessible element. Fiber cement corrugated tiles are examples of some products derived from this class of material. Besides being the object of study of this work, these are of cement-based matrix, commonly Portland cement, reinforced with fibers, which currently replace asbestos, are vegetables and / or synthetic. However, one of the main defects that this product presents is related to water permeability, and the appearance of moisture on the underside of the tile may be tolerated, as long as it does not cause too much staining or the formation of water droplets. It is important to note that porous materials may have a significant water absorption capacity as a function of pore structure, quantity and pore size, and the fiber cement tiles, as well as the inherent porosity of the product, have voids in the low-adhesion regions of the fiber interface / matrix, due to the hydrophobic character of the fibers. This study aimed to generate contributions on the effect of water repellent agents on previously processed tiles in order to minimize water permeability, reducing their accessibility through the voids of the fiber / matrix interface, replacing the commercial alternatives of waterproofing and paints treatments surface. The methodology was based on analyzes of the characteristics of asbestos-free fibre cement tiles, evaluating water absorption, apparent porosity, pore size distribution, flexural strength, permeability to water without and with continuous flow and microstructural analysis of samples treated by immersion in aqueous solutions of water repellents before and after accelerated aging test. The results have shown that immersion baths with silicone based hydrophobizing agents with siloxane and silane with copolymerized acrylic resin mixture are effective, minimize staining and droplet formation, and that such a treatment method can be applied industrially.